ANALISIS KINERJA KEUANGAN BANK SYARIAH MENGGUNAKAN SHARIA CONFORMITY AND PROFITABILITY (SCnP) - Ubaidillah, Ubaidillah; Astuti, Tri Puji (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2020)
This study aims to measure the performance of Islamic banks using the SCnP Model. The population of this study is all Islamic commercial banks registered with the OJK from 2017-2019. The sampling technique used purposive sampling, while the data analysis technique was descriptive. The SCnP model has two variables, namely Shariah Conformity with Islamic Income Ratio indicators, Islamic Investment Ratio and Profit Sharing Ratio and Profitability with Return On Assets (ROA), Return On Equity (ROE) and Profit Margin Ratio indicators. The analysis on the SCnP results is that Islamic banks are spread out in four quadrants (ULQ, LLQ, URQ and LRQ) and recommends a sample of research banks, namely subsidiaries of state-owned banks namely Bank Syariah Mandiri, Bank Negara Indonesia Syariah, Bank Rakyat Indonesia Syariah. The results of the study show that for three years, 2017-2019, the results show that Islamic banks are spread out in only two quadrants, namely the Lower Left Quadrant (LLQ) and the Upper Left Quadrant (ULQ). Keywords: Financial Performance, Islamic Commercial Banks, Shariah Conformity and Profitability (SCnP) Model Abstrak Penelitian ini bertujuan untuk mengukur kinerja bank syariah dengan menggunakan SCnP Model. Populasi penelitian ini adalah semua bank umum syariah yang terdaftar di OJK dari tahun 2017-2019. Teknik pengambilan sampel menggunakan purposive sampling, sementara teknik analisis data berupa deskriptif. Model SCnP memiliki dua variabel, yaitu Shariah Conformity dengan indikator Islamic Income Ratio, Islamic Investment Ratio dan Profit Sharing Ratio dan Profitability dengan indikator Return On Assets (ROA), Return On Equity (ROE) dan Profit Margin Ratio. Analisis pada hasil SCnP yaitu, bank syariah tersebar dalam empat kuadran (ULQ, LLQ, URQ dan LRQ) dan merekomendasikan sampel bank penelitian yaitu anak perusahaan dari bank BUMN yakni Bank Syariah Mandiri, Bank Negara Indonesia Syariah, Bank Rakyat Indonesia Syariah. Hasil dari penelitian menunjukkan selama tiga tahun yaitu 2017-2019 menunjukkan hasil bahwa bank syariah tersebar dalam dua kuadran saja, yaitu Lower Left Quadrant (LLQ) dan Upper Left Quadrant (ULQ). Kata kunci: Kinerja Keuangan, Bank Umum Syariah, Shariah Conformity and Profitability (SCnP) Model